Commentary on "Reflections on culture, structure and function of an intensive support service centred on positive behavioural support". Issue 4 (3rd October 2016) - Toogood, Sandy
Abstract : Purpose: The purpose of this paper is to provide a commentary on Patterson and Berry's paper "Reflections on culture, structure and function of an intensive support service centred on positive behavioural support". Design/methodology/approach: This paper reviews key ideas presented in Patterson and Berry's article relative to the recent history of service delivery in the UK and the growing interest being shown in positive behaviour support. Findings: Patterson and Berry's article adds to a modest literature on specialist support services and should stimulate further descriptions of service models and the concepts underpinning them. Originality/value: The literature on specialist support service models is limited and this addition should be relevant to a wide range of clinicians, consumers and commissioners.